2015
DOI: 10.1063/1.4930891
|View full text |Cite
|
Sign up to set email alerts
|

High strain-rate magnetoelasticity in Galfenol

Abstract: This paper presents the experimental measurements of a highly magnetoelastic material (Galfenol) under impact loading. A Split-Hopkinson Pressure Bar was used to generate compressive stress up to 275 MPa at strain rates of either 20/s or 33/s while measuring the stress-strain response and change in magnetic flux density due to magnetoelastic coupling. The average Young's modulus (44.85 GPa) was invariant to strain rate, with instantaneous stiffness ranging from 25 to 55 GPa. A lumped parameters model simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Magneto-elasticity occurs in Galfenol, which is an alloy consisting of iron doped with the metal gallium. Doumann et al have observed that Galfenol is able to turn up to 70% of mechanical energy into magnetic energy [81]. The findings might enable, for example, the development of novel type of collision detectors for vehicle applications.…”
Section: Harvesting Of Kinetic Energymentioning
confidence: 99%
“…Magneto-elasticity occurs in Galfenol, which is an alloy consisting of iron doped with the metal gallium. Doumann et al have observed that Galfenol is able to turn up to 70% of mechanical energy into magnetic energy [81]. The findings might enable, for example, the development of novel type of collision detectors for vehicle applications.…”
Section: Harvesting Of Kinetic Energymentioning
confidence: 99%
“…Fe–Ga alloy (galfenol) is an attractive magnetostrictive material for energy-harvesting devices, sensors and actuators. It has good properties, such as a very large magnetostriction coefficient, and excellent mechanical properties [ 1 , 2 , 3 , 4 , 5 , 6 ]. The alloy exhibits significant magnetocrystalline anisotropy and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the emphasis shifted to a full description of the solid-state system and the study of related subsystems [4][5][6][7][8][9][10][11][12] . The variety of interactions between these two subsystems creates a wide range of applications 13 exploiting the fact that in magnetostrictive materials the mechanical stress affects the magnetization orientation and vice versa [14][15][16][17][18][19][20][21] . For instance, the mechanical stress produced by an acoustic wave can drive magnetization dynamics and excite magnons in such materials if the frequency of lattice vibrations matches the eigenexcitations of the spin system 22,23 .…”
Section: Introductionmentioning
confidence: 99%